Photorefractive direct laser writing. (23rd February 2016) - Vittadello, Laura; Zaltron, Annamaria; Argiolas, Nicola; Bazzan, Marco; Rossetto, Nicola; Signorini, Raffaella
Abstract: We demonstrate a simple technique to create a large number of arbitrary optical structures in photorefractive Fe-doped lithium niobate (Fe:LN). The technique consists in directly writing with a focused laser beam at visible wavelength the desired optical structures on a sample, taking advantage of the photorefractive effect. Using a computer-controlled translation stage, arbitrary 1D patterns can be recorded allowing diffraction gratings or waveguide arrays to be realized. In contrast to other laser-writing approaches, our method exploits solely the large photorefractive sensitivity of Fe:LN as the mechanism to induce the refractive index change. Thanks to this, commonly available, low power cw lasers are sufficient to obtain the desired structures. The resulting refractive index modulations are characterized by an interferometric technique and positively compared with the one-center photorefractive model. The proposed method offers interesting advantages in terms of simplicity, flexibility and cost effectiveness, making it very interesting for rapid prototyping of complicated diffractive optical elements.